2010
DOI: 10.1007/s10765-010-0854-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined FPPE–PTR Calorimetry Involving TWRC Technique. Theory and Mathematical Simulations

Abstract: Photopyroelectric calorimetry in the front detection configuration (FPPE) was combined with photothermal radiometry (PTR), in order to investigate dynamic thermal parameters of different layers of a detection cell. The layout of the detection cell consists of three layers: directly irradiated pyroelectric sensor, liquid layer, and solid backing material; and the scanning parameter is the thickness of the liquid layer (thermal-wave resonator cavity method). The theory developed for the two techniques indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The conclusion of the previous theoretical paper [19] was that both normalized FPPE and PTR signals (Eqs. 1, 3, 4) depend on the thermal effusivity of the backing material.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…The conclusion of the previous theoretical paper [19] was that both normalized FPPE and PTR signals (Eqs. 1, 3, 4) depend on the thermal effusivity of the backing material.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, for a three-layer detection cell (pyroelectric sensor/liquid layer/semi-infinite solid backing), the theory and mathematical simulations demonstrated that both FPPE and PTR calorimetry give similar information [19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations